The British : their religious beliefs and practices, 1800-1986 - Thomas, Terence (Library of religious beliefs and practices., 1988)
A source book for the study of religions in the nineteenth and twentieth centuries challenging the view that Britain is and has been a predominantly single religion country. This pluralism is shown to apply within Christianity as well as outside.